(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
This case report represents the clinical management of tooth with palato-gingival groove in a right maxillary lateral incisor with endo-perio lesion leading to dento-alveolar abscess and sinus tract. The right maxillary lateral incisor was examined clinico-radiographically. On clinical examination, the offending tooth revealed localized swelling and an intraoral draining sinus pointing on the labial gingiva without any evidence of caries, discoloration and trauma. The palatal surface of lateral incisor showed a groove with mild calculus embedded in it. The radiographic examination revealed periapical radiolucency. This case provides an evidence of morphological defect of tooth. Complete clinical and radiological examination and adequate knowledge of such morphological/ developmental defects of teeth are necessary for recognition and identification especially because of their diagnostic complexity and further consequences.